The ethics of community care - Wilmot, Stephen (Cassell, 1997)
Beginning with an analysis of the general principles of ethics, the author proceeds to consider how those involved in community care might arrive at their own judgements of right and wrong in a variety of given situations. Topics include concepts of autonomy, responsibility and care.